Factors Associated With Weight Gain in People Treated With Dolutegravir. (26th May 2020) - Taramasso, Lucia; Bonfanti, Paolo; Ricci, Elena; Orofino, Giancarlo; Squillace, Nicola; Menzaghi, Barbara; De Socio, Giuseppe Vittorio; Madeddu, Giordano; Pellicanò, Giovanni Francesco; Pagnucco, Layla; Celesia, Benedetto Maurizio; Calza, Leonardo; et al.
Abstract: Background: An unexpected excess in weight gain has recently been reported in the course of dolutegravir (DTG) treatment. The aim of the present study was to investigate whether weight gain differs among different DTG-containing regimens. Methods: Adult naïve and experienced people with HIV (PWH) initiating DTG-based antiretroviral therapy (ART) between July 2014 and December 2019 in the Surveillance Cohort Long-Term Toxicity Antiretrovirals (SCOLTA) prospective cohort were included. We used an adjusted general linear model to compare weight change among backbone groups and a Cox proportional hazard regression model to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for weight increases >10% from baseline. Results: A total of 713 participants, 25.3% women and 91% Caucasian, were included. Of these, 195 (27.4%) started DTG as their first ART regimen, whereas 518 (72.6%) were ART-experienced. DTG was associated with abacavir/lamivudine in 326 participants, tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) in 148, boosted protease inhibitors in 60, rilpivirine in 45, lamivudine in 75, and tenofovir alafenamide (TAF)/FTC in 59. At 6 and 12 months, weight gain was highest among PWH on TDF/FTC+DTG and TAF/FTC+DTG. Baseline CD4 <200 cells/mm 3 (HR, 1.84; 95% CI, 1.15 to 2.96), being ART-naïve (HR, 2.24; 95% CI, 1.24 to 4.18), and treatment with TDF/FTC+DTG (HR, 1.92; 95% CI, 1.23 to 2.98) or TAF/FTC+DTG (HR, 3.80; 95% CI, 1.75 to 8.23) were associated with weight gain >10% from baseline. Higher weight (HR, 0.97 by 1 kg; 95% CI, 0.96 to 0.99) and female gender (HR, 0.54; 95% CI, 0.33 to 0.88) were protective against weight gain. Conclusions: Naïve PWH with lower CD4 counts and those on TAF/FTC or TDF/FTC backbones were at higher risk of weight increase in the course of DTG-based ART.